The effect of cycling position on the lower-limb kinematics during the run in triathletes - Moulin, M.; Grimont, J.; Touil, R.; Dewolf, A. H. (HAL Open Science, 2024)
Triathlon is a multisport in which the transition between the phases of a triathlon is a unique feature of this sport. It has already been showed that the run session after cycling may affect performance but also injury risk. Indeed, up to 70% of triathletes have been seen to run at speeds 10% below their normal running speed over the first 500-1000m following cycling in an Olympic triathlon. Also, Rendos et al. (2013) showed that 30 min cycling induces changes in running kinematics of the pelvis, and hip, that may increase the risk for lower extremity injuries. In particular, these authors reported an increase in anterior pelvic tilt and a reduced hip extension in running following cycling. They emitted the hypothesis that those changes were related to the position on the bike causing tightness in the anterior musculature.